(untitled) (مجلة البحوث الأكاديمية, 2026)
A multi-technique study of copolyesters V – VII reveals that molecular weight distribution (polydispersity index, PDI) governs polymer properties more strongly than absolute molecular weight. Narrow distributions promote uniform crystallization, enhancing thermal stability, mechanical strength, surface organization, and interfacial properties, whereas broad distributions lead to heterogeneous structures and reduced consistency. Copolyester VII, with moderate molecular weight (30,000 g mol⁻¹) and narrow PDI (1.20), achieved optimal thermal stability (Tₘ = 582 °C), high crystallinity (65%, 45.2 nm crystallite size), hydrophobicity (contact angle = 93.76°), and tensile strength (72.5 MPa), demonstrating the advantage of distribution control over molecular weight maximization. Copolyesters V and VI illustrate how moderate molecular weight or broad distributions can tailor surface or processing properties, respectively. Mechanistic analysis shows that distribution uniformity dictates crystallization kinetics and structural order, providing predictive structure–property relationships. These insights enable rational material selection for high-performance, surface-critical, or processing-intensive applications while reducing synthesis complexity, resource consumption, and environmental impact. This work establishes molecular weight distribution as a key parameter for designing next-generation, sustainable polymer materials.